Who Are the Net Food Importing Countries? - Ng, Francis; Aksoy, M. Ataman (World Bank, Washington, DC, 2012)
The purpose of this paper is to update the information on net food importing countries, using different definitions of food, separating countries by their level of income, whether they are in conflict and whether they are significant oil exporters. The study also estimates the changes in net food importing status of these countries over the last two and a half decades, and, most important, the study measures the relative importance of these net food imports in the import basket of the countries. Our results show that while many low-income countries are net food importers, the importance and potential impact of the net food importing status has been highly exaggerated. Many low-income countries that have larger food deficits are either oil exporters or countries in conflict. Food deficits of most low-income countries are not that significant as a percentage of their imports. Our results also show that only 6 low-income countries have food deficits that are more than 10 percent of their imports. Last two decades have seen a significant improvement in the food trade balances of low-income developing countries. SSA low-income countries are an exception to this trend. On the other hand, there are a group of countries which are experiencing civil conflicts which are large importers of food, and these countries can not meet their basic needs. They also need special assistance in the distribution of food within their boundaries. Therefore, one should modify the WTO Ministerial Declaration, and focus on these conflict countries rather than the broad net food importers.